KEMAMPUAN HARGA SAHAM DALAM MENCERMINKAN EKSPEKTASI LABA MENDATANG: LABA PERMANEN, LABA TRANSITORI, DAN ARUS KAS - Stefanus Ronie Kristiawan; Yusni Warastuti (Jurnal Akuntansi Bisnis, 2013)
This study was conducted to provide empirical evidence about the effect of earnings information consisting of permanent and transitory income and operating cash flow to earnings and whether the stock price is able to reflect the earnings and cash flows have been included in the upcoming earnings expectations. The sample used in this study 81 companies included in the group LQ45 second half period January 2004-July 2007. This study uses two models (prediction and pricing). Results of this study indicate that current earnings and operating cash flows have a significant positive effect on future earnings. While stock prices are not able to reflect the information used in the model predictions. Investors underweight the information permanent income, transitory income, and operating cash flow.